2020
DOI: 10.21037/jtd-20-2652
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of cough after uniportal video-assisted thoracoscopic pulmonary resection

Abstract: Background: Cough is one of the shared complications after lung surgery. In this study, a prospective analysis was conducted for exploring the risk factors of persistent cough after uniportal video-assisted thoracoscopic pulmonary resection. Methods: One hundred thirty-five patients with pulmonary nodules who underwent surgical treatment in the same surgical group from November 2019 to January 2020 were enrolled in this prospective study.The severity of cough and its impact on patients' quality of life before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 40 publications
5
16
0
Order By: Relevance
“…In this experiment, double lumen endotracheal intubation under general anesthesia was used to eliminate the bias caused by using different anesthesia methods. Our findings confirmed that the longer the anesthesia was maintained, the more prone the patient was to chronic cough after operation, which was consistent with previous studies ( 31 , 32 ).…”
Section: Discussionsupporting
confidence: 93%
“…In this experiment, double lumen endotracheal intubation under general anesthesia was used to eliminate the bias caused by using different anesthesia methods. Our findings confirmed that the longer the anesthesia was maintained, the more prone the patient was to chronic cough after operation, which was consistent with previous studies ( 31 , 32 ).…”
Section: Discussionsupporting
confidence: 93%
“…Among them, systematic lymph node dissection, especially the dissection of subcarinal lymph nodes, is one of the most important risk factors. 7 In a previous study, 8 we also confirmed that subcarinal lymph node dissection is an independent risk factor for CAP. Nevertheless, our study has not further elucidated the mechanism of the aggravation of postoperative cough by subcarinal lymph node dissection.…”
Section: Introductionsupporting
confidence: 83%
“…The often complex perioperative factors when performing pulmonary resection prevent researchers from addressing the issue of PIC. A range of reasons are assumed to account for this, including airway infection, asthma, end-bronchial sutures, lymph node dissection, gastrointestinal reflux, postoperative physical deconditioning, and bronchial kink (3,4). Following right upper lobectomy (RUL), the remaining trachea and lungs need to adapt to the new conditions.…”
Section: Introductionmentioning
confidence: 99%